Nurses’ Self-management Experiences in Managing Covid-19 Patients: A Scientific Perspective - Linda, Silvana Evi (GLOBAL HEALTH SCIENCE GROUP, 2024)
The Covid-19 pandemic has placed unprecedented demands on healthcare systems worldwide, with nurses bearing a significant portion of the burden. This paper explores the self-management experiences of nurses working directly with Covid-19 patients. This study aims to examine and understand the self-management experience of nurses, explore its impact on their performance and well-being, and provide insights to enhance future nursing practices and healthcare policies. Through a review of existing literature and qualitative analysis, the study identifies key strategies used by nurses to maintain their physical and mental well-being amidst the challenges of the pandemic. The findings highlight the importance of time management, stress management, self-care, and social support systems in enabling nurses to sustain their roles effectively during the crisis.